Evaluation of modified Congo red agar for detection of biofilm produced by clinical isolates of methicillin–resistance Staphylococcus aureus - Shamsudin, Mariana Nor; Atshan, Salman Sahab; Neela, Vasantha Kumari; Sekawi, Zamberi (Academic Journals, 2009)
Methicillin resistance Staphylococcus aureus (MRSA) notoriety is not limited to nosocomial or community acquired infection but is so much the cause of biofilm related infection. Use of highly selective or differential medium, published Congo Red Agar (PCRA) has important shortcomings such as variations in black pigment formation while the intracellular adhesion locus (ica) gene required for biofilm production received equivocal outcomes since contradictory results. The evaluation of modified Congo Red Agar (MCRA) was conducted based on the characteristics of 100 MRSA isolated from different clinical samples and controls. All MRSA isolates showed presence of icaA and icaD genes by the PCR method and then formed intense black pigmented colonies on the Modified Congo Red Agar with increased times in contrast growth of 78% MRSA strains were exhibited black pigmentation on the published CRA but pigmentation decreased with time. The phenotypic coloration on agar improved upon modification of agar ingredients. The reduction in the concentration of several agar constituents resulted in permanent formation of intense black pigment in isolates with ica A and D genes, without any decreased in pigmentation over time. The agar constituent modification allowed stability of black pigment formation and also reduced agar preparation cost.